Original paperThe influence of vitamin D receptor gene polymorphism on basal cell carcinoma development in the Polish population - Lesiak, Aleksandra; Wódz-Naskiewicz, Karolina; Pawliczak, Rafał; Rogowski-Tylman, Michał; Sysa-Jędrzejowska, Anna; Sobjanek, Michał; Włodarkiewicz, Adam; Narbutt, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction: Basal cell carcinomas (BCC) are the most common cancers in Caucasian populations. Their pathogenesis is not fully known, but genetic and environmental factors are relevant. Among genetic disturbances, genes encoding intracellular signalling pathways and regulatory proteins are considered the most important. In recent years associations between polymorphisms in the VDR gene and different internal organs and skin neoplasms have been found. Aim: To assess the frequency of FokI, BsmI, TaqI and ApaI polymorphisms in the VDR gene in patients with BCC. Material and methods: VDR polymorphisms were assessed in 142 BCC patients using PCR-RFLP. Results: The presence of TT genotype in FokI polymorphism was linked to the highest risk for BCC development (OR = 10.145, p < 0.001). Other genotypes such as GT in ApaI and TT and TC in TaqI also statistically increased the risk for BCC, but these associations were weaker. No correlation between the presence of any analysed polymorphisms and constitutive features such as hair or eye colour or skin phototype was found. Conclusions: The obtained results confirm the role of the polymorphisms in the VDR gene in the development of basal cell carcinomas in patients of Polish origin.